Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyg.2021.767507
|View full text |Cite
|
Sign up to set email alerts
|

Remote Assessment of Depression Using Digital Biomarkers From Cognitive Tasks

Abstract: We describe the design and evaluation of a sub-clinical digital assessment tool that integrates digital biomarkers of depression. Based on three standard cognitive tasks (D2 Test of Attention, Delayed Matching to Sample Task, Spatial Working Memory Task) on which people with depression have been known to perform differently than a control group, we iteratively designed a digital assessment tool that could be deployed outside of laboratory contexts, in uncontrolled home environments on computer systems with wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…70 Several studies have demonstrated the potential of using digital biomarkers (based on sensor data from wearable devices or mobile apps) for the prediction and detection of depression. [71][72][73] There are also opportunities to develop online and mobile apps for the prevention of depression. 74 However, it should be noted that unlike conditions such as diabetes, where significant adoption of digital technologies has been observed, depression is more complex due to the unique challenges associated with the clinical management of the disorder (eg, poor mental health literacy, stigma, and the lack of objective tools for assessment and diagnosis).…”
Section: Rapid Growth Of Digital Health Technologiesmentioning
confidence: 99%
“…70 Several studies have demonstrated the potential of using digital biomarkers (based on sensor data from wearable devices or mobile apps) for the prediction and detection of depression. [71][72][73] There are also opportunities to develop online and mobile apps for the prevention of depression. 74 However, it should be noted that unlike conditions such as diabetes, where significant adoption of digital technologies has been observed, depression is more complex due to the unique challenges associated with the clinical management of the disorder (eg, poor mental health literacy, stigma, and the lack of objective tools for assessment and diagnosis).…”
Section: Rapid Growth Of Digital Health Technologiesmentioning
confidence: 99%
“…Many related works exist in the literature about biomarkers for various physiological and psychological states [7,8,9,10,11,12]. In [7], the authors examined the behavioral markers to track physical activity following hospital discharge via data from wearable devices.…”
Section: Related Workmentioning
confidence: 99%
“…In [8], researchers examined biomarkers of depression state outside of the laboratory. Similar to [7], they collected data with wearable devices and stateof-the-art questionnaires, namely Patient Health Questionnaire (PHQ-9), as a ground truth.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to accurately and dynamically assess the attention bias of patients with depression through traditional structured clinical interviews and self-report measures. To provide an early warning for patients with depression more objectively, intelligently, and accurately, the application of "digital biomarkers" under specific tasks captured by digital equipment in the field of depression screening is attracting the attention of more and more scholars [17][18][19]. Digital biomarkers are defined as objective, quantifiable physiological and behavioral data that are collected and measured through digital devices [20].…”
Section: Introductionmentioning
confidence: 99%